2010
DOI: 10.1128/iai.01385-09
|View full text |Cite
|
Sign up to set email alerts
|

Human Brucellosis Is Characterized by an Intense Th1 Profile Associated with a Defective Monocyte Function

Abstract: In animal models, a defective Th1 response appears to be critical in the pathogenesis of brucellosis, but the Th1 response in human brucellosis patients remains partially undefined. Peripheral blood from 24 brucellosis patients was studied before and 45 days after antibiotherapy. Twenty-four sex-and age-matched healthy donors were analyzed in parallel. Significantly increased levels of interleukin 1␤ (IL-1␤), IL-2, IL-4, IL-6, IL-12p40, gamma interferon (IFN-␥), and tumor necrosis factor alpha (TNF-␣), but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
44
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 49 publications
(66 reference statements)
6
44
1
3
Order By: Relevance
“…That study also showed that high TNFα levels were decreased by brucellosis treatment. A recently published study reported results similar to those of Demirdag et al [6].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…That study also showed that high TNFα levels were decreased by brucellosis treatment. A recently published study reported results similar to those of Demirdag et al [6].…”
Section: Discussionsupporting
confidence: 82%
“…are intracellular bacteria that release cytokines such as IFN-gamma, IL-2, and TNFα. Activated macrophages and dendritic cells are required for the immune response against Brucella infection [4][5][6]. TNFα has a critical role in macrophage activation, apoptosis, proinflammatory cytokine release, and granuloma formation.…”
Section: Introductionmentioning
confidence: 99%
“…This involves mainly activated antigen-presenting cells (dendritic cells, macrophages) and CD4+, CD8+ T lymphocytes. This is mediated by a Th1 immune response and is considered to be critical for the efficiency of the protective anti-Brucella immune response (Zhan et al, 1993;Rodriguez-Zapata et al, 2010). The activated host antigen-presenting cells release interleukin-12 (IL-12), which causes the differentiation of Th0 cells into Th1 cells that secrete gamma interferon (IFN-γ) and up-regulates macrophage killing mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Acute human brucellosis also raises IL-8 levels (19). Significantly increased levels of IL-4 and IL-6 have been found in untreated brucellosis patients (20).…”
Section: Discussionmentioning
confidence: 99%